Cognitive Impairment in Aging Physicians: Current Challenges and Possible Solutions. Issue 2 (April 2021) - Devi, Gayatri; Gitelman, Darren R.; Press, Daniel; Daffner, Kirk R.
Abstract : Aging physicians are at a higher risk of cognitive impairment, undermining patient safety and unraveling physicians' careers. Neurologists, occupational health physicians, and psychiatrists will participate in both health system policy decisions and individual patient evaluations. We address cognitive impairment in aging physicians and attendant risks and benefits. If significant cognitive impairment is found after an appropriate evaluation, precautions to confidentially support physicians' practicing safely for as long as possible should be instituted. Understanding that there is heterogeneity and variability in the course of cognitive disorders is crucial to supporting cognitively impaired, practicing physicians. Physicians who are no longer able to practice clinically have other meaningful options.